Why do leaders matter? The role of expert knowledge - Amanda H. Goodall; Lawrence M. Kahn; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2008)
Why do some leaders succeed while others fail? This question is important, but its complexity makes it hard to study systematically. We examine an industry in which there are well-defined objectives, small teams, and exact measures of leaders' characteristics. We show that a strong predictor of a leader's success in year T is that person's own level of attainment, in the underlying activity, in approximately year T-20. Our data come from 15,000 professional basketball games. The effect on team performance of the coach's 'expert knowledge' is large and is discernible in the data within 12 months of his being hired.
urn:nbn:de:101:1-2008071185
Keywords: J24; 650; Organizational performance; firms; leadership; fixed-effects; productivity; Führungstheorie; Sachverständige; Ausbilder; Sportökonomik; Produktivität; Erfolgsfaktor; USA